Clinical characterization and molecular mechanisms of statin myopathy. (August 2008) - Toth, Peter P; Harper, Charles R; Jacobson, Terry A
Myopathy has been reported in a small percentage of statin-treated patients for the past 30 years, but the etiologic mechanisms for inducing muscle injury have not yet been fully characterized. Statin-induced myopathy is now understood to be a heterogeneous condition that may be due to: mechanisms of the drug itself; interactions with other drugs; or genetic, metabolic and immunological vulnerabilities in individual patients. In some cases, statins may unmask latent conditions (e.g., asymptomatic baseline myopathy) that predispose patients to muscle toxicity. The definitions, epidemiology, clinical features, risk factors and proposed mechanisms of statin-induced myopathy are reviewed. Muscle metabolism can be adversely impacted by statin therapy, including changes in fatty acid oxidation, possibly reduced coenzyme Q10 biosynthesis, and increased myocyte protein degradation via the activity of atrogin-1 and the ubiquitin–proteasome pathway. Statin therapy may also activate a variety of autoimmune phenomena that potentiate myocellular injury. Improving our understanding of statin-induced myopathy is a high clinical priority given the large number of patients eligible for statin therapy and the fact that the development of myalgia and myopathy are leading reasons cited by patients for statin discontinuation.